The The Influence of Financial Literacy, Risk Perception, Herding, Loss Aversion, Anchoring, And Income on Gold Investment Decisions at PT. Pegadaian (Persero) - Lestari, Faidah Indah; Isbanah, Yuyun (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
The investment interest in Indonesia is rising in line with the society's awareness on the benefit of investment, especially gold investment. Investors act rationally or irrationally in making investment decisions. The aim of this research is to study the effect of financial literacy, risk perception, herding, loss aversion, anchoring and income to the decision of gold investment at PT. Pegadaian. This is a quantity experiment with the customer of PT. Pegadaian who used the gold investment as a population and sample of this research. Using the accidental sampling technique, there are 100 respondents. Data collection using a direct and online questionnaire. The Structural equation model partial least square method with the SmartPLS 3.0 software used to analyze the data collected. The results show that financial literacy affects investment decisions. Respondents have a fairly high level of education and moderately high association of financial literacy. While the risk perception, herding, loss aversion, anchoring and income are not affecting the investment decisions.